The effect of nordic walking with poles with an integrated resistance shock absorber on muscle stiffness and elasticity indicators in postmenopausal women - Wochna, Krystian; Stemplewski, Rafał; Leszczyński, Piotr; Kocur, Piotr (Frontiers in Physiology, 2025)
IntroductionUnderstanding the impact of physical activity and its relationship with changes in the biomechanical parameters of the myofascial system at different stages of menopause is important for planning and implementing effective action strategies. The reduction in elasticity and increase in stiffness in upper limb muscles, including in particular tonic muscles, lead to mobility limitations and increased risk of pain. Therefore, the aim of the present study was to evaluate and compare the impact of different types of Nordic walking training on muscle stiffness and elasticity indicators in postmenopausal women.MethodsThirty women were randomly assigned to two training groups using different kind of poles and completed 8 weeks of training program. Before starting the training programs and after their completion, total fat, lean body mass were measured, along with muscle stiffness and elasticity indicators. Main calculations was based on 2 × 2 analysis of variance ANOVA with repeated measures.ResultsThe significant interaction effect was found in differences between the two groups of women with respect to the upper trapezius muscle (p = 0.037). Significant “time” effects were observed for the triceps brachii and brachioradialis muscles (p = 0.032, p = 0.028, respectively) as a result of increased post-intervention muscle stiffness for all participants.DiscussionThe upper trapezius may be the muscle most strongly engaged during the training, which may lead to sustained passive changes and should have an influence on recommendations on the use of RSA poles in population of postmenopausal women in selected clinical conditions. NW training with RSA poles may be an alternative to traditional NW training for individuals whose physical fitness and health status allows them to engage in such training.